RELATIONSHIP OF LHX3 GENE POLYMORPHISM TO FERTILITY RATE IN LOCAL AND SHAMI GOATS: RELATIONSHIP OF LHX3 GENE POLYMORPHISM TO FERTILITY RATE IN LOCAL AND SHAMI GOATS (Iraqi Journal of Market Research and Consumer Protection, 2022)
ABSTRACTThe study was conducted at the ruminant research station of the general commission for agricultural research/Ministry of Agriculture, as well as the laboratory of genetic resources of the department of livestock/Ministry of Agriculture and the laboratory of the college of agriculture engineering science, with the aim of determine the genotypic of the expression region (intron 2 and part of exon 3) of the LHX3 gene And its relationship to the fertility rate in local and Shami goats. For this purpose, the RFLP technique was used, and the percentages of genotypes for the LHX3 gene in the local goat sample were 29.17, 50.00, 20.83 for the TT, AT, and AA genotypes, respectively, while in the Shami goats, the genotypes of the LHX3 gene in the goat sample were 29.17, 50.00, and 20.83 Shami 44.00, 56.00 and 0.00 for the TT, AT, and AA genotypes, respectively, and it was found that there was a significant effect of the multiple genotypes of the LHX3 gene on the fertility rate in local and Shami goats. It was found that the important reproductive trait in goats is the fertility trait, which is affected by several aspects, including environmental And administrative as well as genetic influences, as I found a lot of genetic mutations, As the percentage of twins reaches 42% in goats, according to the breed, through genetic selection assisted by markers (MAS). The values of the genetic equivalent for fecundity of goats are approximately 0.02 - 0.15.